Toad-headed agama (Phrynocephalus mystaceus Pallas): The state of the population on the Sarykum sand massif (Dagestan, Russia) - G.V. Polynova; O.E. Polynova (Учёные записки Казанского университета: Серия Естественные науки)
This article provides a detailed description and analysis of two settlements of toad-headed agamas (Phrynocephalus mystaceus Pall.) on the Sarykum sand massif based on the data collected during the first ten days of May 2019 (105 individuals – 31 males, 49 females, and 25 immature individuals) and 2021 (115 individuals – 26 males, 22 females, and 67 immature individuals), respectively. The age and sex structure of both settlements was studied to assess the state of the species population. All individuals had their body length measured and were labelled, either permanently or temporarily. The statistical significance of the results obtained was determined using the nonparametric Mann-Whitney test. It was revealed that both settlements had the following sex and age groups: immature individuals and mature males and females. Mature individuals of both sexes were represented by two age stages: those aged two years, as well as three years and older. The core of the population consisted of young individuals and males and females aged two years. In the first settlement, mature individuals were more abundant, and females dominated among them. In the second settlement, immature individuals prevailed, and males dominated among mature individuals. The local density of the second settlement inaccessible to tourists was 2.6 times higher. The configurations of the sex and age pyramids showed that the first settlement affected by the recreational load was in the process of reduction, while the second settlement with no anthropogenic input turned out to be stable. It was concluded that the recreational load and habitat overgrowth speak for the need to monitor the toad-headed agama population of the Sarykum sand massif.